TEACHER’S AND STUDENT’S PERCEPTIONS OF CORRECTIVE FEEDBACK IN TEACHING SPEAKING (English Education Journal, 2015)
The purposes of this study were to find out the types of the spoken errors commonly made by the students in speaking, knowing the reasons do the students make same errors, describing how English teachers use corrective feedback to refine students’ errors, exploring the types of corrective feedback do the students mostly like, explaining the teachers’ and students’ perceptions towards corrective feedback.The types of this study was descriptive qualitative study. The findings indicated that errors mostly made by the students were pronunciation error, grammatical error and lexical error, why did they make same errors because the students got fossilization, corrcetive feedbacks were used to refine students speaking were explicit correction, repetition and reformulation, corrective feedbacks that the students mostly like were explicit correction, repetition and pronunciation, the teachers perceptions towards corrective feedback were corrective feedback was to know the lacks of the students speaking, the teachers could give the students feedbacks in order not to be fossilized. by giving feedback appropraitely it was believed the students would not be fossilized. The students’ perceptionson corrective feedback were they had very good responses about corrective feedback that were given by the teachers in the classroom.